Toward the Adaptive Reuse of Vernacular Architecture: Practices from the School of Porto - David Ordóñez-Castañón; Teresa Cunha Ferreira (Heritage, 2024)
Strategies for the adaptive reuse of vernacular architecture are of utmost importance in the current context of social, economic, and environmental vulnerability. This article examines the design strategies of adaptive reuse in three cases of renowned architects of the so-called School of Porto developed across the second half of the 20th century, specifically between 1956 and 1991. The paper aims to introduce a new and deeper knowledge of the selected practices by critically documenting the whole process of the intervention (before, during, after) and not only the final result, as is common practice in specialized publications. The research methodology combines the bibliographical and archival research and interpretation of diverse graphic, photographic, and textual documentation with the production of analytical drawings. The demolitions/additions color code (black/yellow/red) is applied to plans, sections, and elevations as an essential tool for understanding and communicating the transformations undertaken. The selected case studies are Além House (1956–1967) by Fernando Távora, Alcino Cardoso House (1971–1973; 1988–1991) by Álvaro Siza, and the House in Gerês (1980–1982) by Eduardo Souto de Moura. These projects show different strategies of intervention in built heritage, providing lessons on the reactivation of obsolete or abandoned rural constructions with new functions that are compatible with the preservation of their values (historical, landscape, constructive, social, and aesthetic) and guidelines for sustainable reuse.